To find the zeros of the quadratic function \( y = x^2 + 15x + 36 \), we need to solve the equation \( x^2 + 15x + 36 = 0 \).
We can use the quadratic formula, which is given by: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] where \( a = 1 \), \( b = 15 \), and \( c = 36 \).
First, calculate the discriminant: \[ b^2 - 4ac = 15^2 - 4(1)(36) = 225 - 144 = 81 \]
Now, we can plug the values into the quadratic formula: \[ x = \frac{-15 \pm \sqrt{81}}{2(1)} = \frac{-15 \pm 9}{2} \]
This gives us two solutions:
-
For the positive case: \[ x = \frac{-15 + 9}{2} = \frac{-6}{2} = -3 \]
-
For the negative case: \[ x = \frac{-15 - 9}{2} = \frac{-24}{2} = -12 \]
Thus, the zeros of the function are:
- Smaller zero: \( x = -12 \)
- Greater zero: \( x = -3 \)
Final answer:
- smaller zero: \( x = -12 \)
- greater zero: \( x = -3 \)